Act East through India's Northeast: Limits of Neoliberal Strategies towards Developing an Underdeveloped Region. (March 2022) - Patgiri, Rubul; Gogoi, Dilip
One of the major objectives of the Look East, now rechristened as Act East Policy, of India is to develop the geographically and economically isolated region of Northeast India by economically integrating it with the neighbouring regions of South East Asia through neoliberal economic intervention. In view of this, the present article tries to analyse the rationale of such neoliberal-centric development model for the Northeast India as envisaged under the Look (Act) East Policy, existing gaps in the present policy framework and its impact. It argues that so far, such a strategy has brought very little dividend for the Northeast and may be at odds with some of the existing political, economic and social realities of the region. The article finally concludes by arguing that resources and interests of the region must be protected while trying to expose the region to global market economy for greater economic prosperity.